Vortices on a sphere - Alobaidi, G.; Haslam, M. C.; Mallier, R. (Mathematical Modelling and Analysis, 2006)
We consider flows on a spherical surface and use a streamfunction formulation to derive a nonlinear equation governing steady‐state flows in that geometry. We present some new vortex solutions to this equation.First Published Online: 14 Oct 2010